Cybersecurity in Banking and Finance : Navigating the Digital Threat Landscape - Poli Reddy Reddem (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the critical landscape of cybersecurity in the banking and finance sector, addressing the unique challenges financial institutions face in an increasingly digital world. It delves into the Cybersecurity Trilemma of high-value targets, complex IT infrastructure, and stringent regulatory compliance, highlighting the sector’s vulnerability to sophisticated cyber threats. The article outlines key security measures, including data encryption, access control, data loss prevention, regular security audits, and incident response planning, supported by current industry statistics. It navigates the complex regulatory environment, discussing major compliance requirements such as GDPR, HIPAA, PCI DSS, GLBA, and CCPA. Finally, the article presents a framework for building resilient cybersecurity, emphasizing risk assessment, security awareness training, threat intelligence, continuous improvement, and regulatory collaboration. It provides financial institutions with a roadmap to safeguard their assets and maintain customer trust in the face of evolving cyber threats.